Ancient Greece : from the Mycenaean palaces to the age of Homer (Edinburgh Leventis studies, 2010)
1. The formation of the Mycenaean palace / James C. Wright -- 2. Wanaks and related power terms in Mycenaean and later Greek / Thomas G. Palaima -- 3. Mycenaean palatial administration / Cynthia W. Shelmerdine -- 4. The subjects of the wanax : aspects of Mycenaean social structure / John T. Killen -- 5. [Anax] and [Basileys] in the Homeric poems / Pierre Carlier -- 6. Kin-groups in the Homeric epics (summary) / Walter Donlan -- 7. The Mycenaean heritage of Early Iron Age Greece / Oliver Dickinson -- 8. Coming to terms with the past : ideology and power in Late Helladic IIIC / Joseph Maran -- 9. Late Mycenaean warrior tombs / Sigrid Deger-Jalkotzy -- 10. The archaeology of basileis / Alexander Mazarakis Ainian -- 11. From Late Bronze Age to Early Iron Age copper metallurgy in mainland Greece and offshore Aegean Islands / Maria Kayafa -- 12. Ethne in the Peloponnese and Central Greece / Catherine Morgan -- 13. Gift exchange : modern theories and ancient attitudes / Beate Wagner-Hasel -- 14. Basileis at sea : elites and external contacts in the Euboean Gulf region from the end of the Bronze Age to the beginning of the Iron Age / Jan Paul Crielaard -- 15. Aspects of the 'Italian connection' / David Ridgway -- 16. From the Mycenaean qa-si-re-u to the Cypriote pa-si-le-wo-se : the basileus in the kingdoms of Cyprus / Maria Iacovou -- 17. Phoenicians in Crete / Nicholaos Chr. Stampolidis and Antonios Kotsonas -- 18. From kings to demigods : epic heroes and social change c. 750-600 B.C. / Hans van Wees -- 19. Religion, basileis and heroes / Carla Antonaccio -- 20. Cult activity on Crete in the early dark age : changes, continuities and the development of a 'Greek' cult system / Anna Lucia D'Agata -- 21. The rise and descent of the language of the Homeric poems / Michael Meier-Brugger -- 22. Homer and oral poetry / Edzard Visser -- 23. Some remarks on the semantics of [Anax] in Homer / Martin Schmidt -- 24. Historical approaches to Homer / Kurt A. Raaflaub -- 25. The palace of Iolkos and its end / Vassiliki Adrimi-Sismani -- 26. Early Iron Age elite burials in East Lokris / Fanouria Dakoronia -- 27. Athens and Lefkandi : a tale of two sites / Irene S. Lemos -- 28. The Early Iron Age in the Argolid : some new aspects / Alkestis Papadimitriou -- 29. The world of Telemachus : western Greece 1200-700 B.C. / Birgitta Eder -- 30. Knossos in Early Greek times / J.N. Coldstream -- 31. Praisos : political evolution and ethnic identity in eastern Crete c. 1400-300 B.C. / James Whitley -- 32. The gilded cage? : settlement and socioeconomic change after 1200 B.C. : a comparison of Crete and other Aegean regions / Saro Wallace -- 33. Homeric Cyprus / Vassos Karageorghis.